Differential Effects of Tissue-Specific Deletion of BOSS on Feeding Behaviors and Energy Metabolism. - Kohyama-Koganeya, A.; Kurosawa, M.; Hirabayashi, Y. (PLoS ONE, 2015)
Food intake and energy metabolism are tightly controlled to maintain stable energy homeostasis and healthy states. Thus, animals detect their stored energy levels, and based on this, they determine appropriate food intake and meal size. Drosophila melanogaster putative G protein-coupled receptor, Bride of sevenless (BOSS) is a highly evolutionarily conserved protein that responds to extracellular glucose levels in order to regulate energy homeostasis. To address how BOSS regulates energy homeostasis, we characterized a boss mutant by assessing its food intake and stored energy levels. Boss mutants exhibited increased food intake but decreased stored triacylglyceride levels. Using boss-GAL4 drivers, we found that boss is expressed in select tissues that are involved in nutrient sensing and food intake, in a subset of neurons in brain and chemosensory organs, in fat body, and in endocrine cells in gut (enteroendocrine cells). Flies with tissue-specific boss knockdowns in these tissues had abnormal stored energy levels and abnormal food intake. These results suggest that BOSS in either neurons or peripheral nutrient-sensing tissues affects energy homeostasis in ways that relate to the sensing of nutrients and regulation of food intake.